2012
DOI: 10.1177/1363459312460700
|View full text |Cite
|
Sign up to set email alerts
|

A confusion of tenses: Health screening and time

Abstract: The article seeks to contribute to a re-evaluation of the role played by the contemporary health screen by exploring its relation to tense and time. Mobilizing data around operational aspects of screening for type 2 diabetes (T2D) alongside more general historical and conceptual perspectives, it challenges implicit assumptions that the screen represents either a momentary 'cut' in a longer process or a singular event with its own durational integrity. In contrast, the article argues, two distinct kinds of temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Though a focus on time is relatively rare in health research (Stronge, ), biomedical research reports unstable and non‐linear processes in healthy lifestyle practices (e.g., Dombrowski, Knittle, Avenell, Araújo‐Soares, & Sniehotta, ). A similar pattern is found in the context of ill health.…”
Section: Time In Health and Lifestyle Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Though a focus on time is relatively rare in health research (Stronge, ), biomedical research reports unstable and non‐linear processes in healthy lifestyle practices (e.g., Dombrowski, Knittle, Avenell, Araújo‐Soares, & Sniehotta, ). A similar pattern is found in the context of ill health.…”
Section: Time In Health and Lifestyle Researchmentioning
confidence: 99%
“…Stronge's () research with people undertaking health screening also identified tensions arising from complex temporalities, as feared futures and past histories were experienced in an uncertain present for people awaiting screening‐test results. People negotiating lifestyle advice after coronary heart disease also showed a simultaneous drawing on of past, present, and future capacities.…”
Section: Time In Health and Lifestyle Researchmentioning
confidence: 99%
See 3 more Smart Citations